The moderating effect of risk tolerance on the intention of profit-sharing investment account holders to patronise Islamic banks in Nigeria: a proposed framework - Isah, Ya'u; Rosman, Romzie; Sharofiddin, Ashurov (2020)
IBs have 3 major sources of funding their activities: equity provided by their shareholders, transaction deposits and investment deposit by PSIAHs (Yahaya et. al, 2016) • Of all the 3 sources, PSIAHs are the most vulnerable that require special protection because, shareholders’ interest is protected by the banks’ directors, and transactional deposits are guaranteed by the bank and repaid on demand • PSIAHs on the other hand have no representation on the banks’ board to protect their interest, and their funds is not guaranteed which exposes them to the possibility of losing part or all their investment (Alhammadi, et. al, 2018) • The policies set by the IBs’ board of directors are more likely to reflect the risk-return preference of their shareholders than those of PSIAHs (Alhammadi, et. al, 2018)